A Pair of Cobalt(III/IV) Terminal Imido Complexes - Mao, Weiqing; Fehn, Dominik; Heinemann, Frank Wilhelm; Scheurer, Andreas; Munz, Dominik; Meyer, Karsten (Angewandte Chemie International Edition, 2021)
The reaction of the cobalt(I) complex [(TIMMNmes)Co-I](BPh4) (2) (TIMMNmes=tris-[2-(3-mesitylimidazolin-2-ylidene)methyl]amine) with 1-adamantylazide yields the cobalt(III) imido complex [(TIMMNmes)Co-III(NAd)](BPh4) (3) with concomitant release of dinitrogen. The N-anchor in diamagnetic 3 features an unusual, planar tertiary amine, which results from repulsive electrostatic interaction with the filled d(z(2))-orbital of the cobalt ion and negative hyperconjugation with the neighboring methylene groups. One-electron oxidation of 3 with [FeCp2](OTf) provides access to the rare, high-valent cobalt(IV) imido complex [(TIMMNmes)Co-IV(NAd)](OTf)(2) (4). Despite a half-life of less than 1 h at room temperature, 4 could be isolated at low temperatures in analytically pure form. Single-crystal X-ray diffractometry and EPR spectroscopy corroborate the molecular structure and the d(5) low-spin, S=1/2 , electron configuration. A computational analysis of 4 suggests high covalency within the Co-IV=NAd bond with non-negligible spin density located at the imido moiety, which translates into substantial triplet nitrene character.
CRIS-Team WoS Importer:2021-06-25

From Divalent to Pentavalent Iron Imido Complexes and an Fe(V) Nitride via N-C Bond Cleavage - Keilwerth, Martin; Mao, Weiqing; Jannuzzi, Sergio A. V.; Grunwald, Liam; Heinemann, Frank Wilhelm; Scheurer, Andreas; Sutter, Jörg; Debeer, Serena; Munz, Dominik; Meyer, Karsten (Journal of the American Chemical Society, 2022)
As key intermediates in metal-catalyzed nitrogen-transfer chemistry, terminal imido complexes of iron have attracted significant attention for a long time. In search of versatile model compounds, the recently developed second-generation N-anchored tris-NHC chelating ligand tris-[2-(3-mesityl-imidazole-2-ylidene)-methyl]amine (TIMMNMes) was utilized to synthesize and compare two series of mid- to high-valent iron alkyl imido complexes, including a reactive Fe(V) adamantyl imido intermediate en route to an isolable Fe(V) nitrido complex. The chemistry toward the iron adamantyl imides was achieved by reacting the Fe(I) precursor [(TIMMNMes)Fe-I(N-2)]+ (1) with 1-adamantyl azide to yield the corresponding trivalent iron imide. Stepwise chemical reduction and oxidation lead to the isostructural series of low-spin [(TIMMNMes)Fe-(NAd)](0,1+,2+,3+) (2(Ad)-5(Ad)) in oxidation states II to V. The Fe(V) imide [(TIMMNMes)Fe(NAd)](3+) (5(Ad)) is unstable under ambient conditions and converts to the air-stable nitride [(TIMMNMes)Fe-V(N)](2+) (6) via N-C bond cleavage. The stability of the pentavalent imide can be increased by derivatizing the nitride [(TIMMNMes)Fe-IV(N)]+ (7) with an ethyl group using the triethyloxonium salt Et3OPF6. This gives access to the analogous series of ethyl imides [(TIMMNMes)Fe(NEt)](0,1+,2+,3+) (2(Et)-5(Et)), including the stable Fe(V) ethyl imide. Iron imido complexes exist in a manifold of different electronic structures, ultimately controlling their diverse reactivities. Accordingly, these complexes were characterized by single-crystal X-ray diffraction analyses, SQUID magnetization, and electrochemical methods, as well as Fe-57 Mossbauer, IR vibrational, UV/vis electronic absorption, multinuclear NMR, X-band EPR, and X-ray absorption spectroscopy. Our studies are complemented with quantum chemical calculations, thus providing further insight into the electronic structures of all complexes.
CRIS-Team WoS Importer:2023-01-27

Ligand Tailoring Toward an Air-Stable Iron(V) Nitrido Complex - Keilwerth, Martin; Grunwald, Liam; Mao, Weiqing; Heinemann, Frank Wilhelm; Sutter, Jörg; Bill, Eckhard; Meyer, Karsten (Journal of the American Chemical Society, 2021)
A new supporting ligand, tris-[2-(3-mesityl-imidazol-2-ylidene)methyl]amine (TIMMNMes), was developed and utilized to isolate an air-stable iron(V) complex bearing a terminal nitrido ligand, which was synthesized by one-electron oxidation from the iron(IV) precursor. Single-crystal X-ray diffraction analyses of both complexes reveal that the metal-centered oxidation is escorted by iron nitride (FeN) bond elongation, which in turn is accompanied by the accommodation of the high-valence iron center closer to the equatorial plane of a trigonal bipyramid. This contrasts with the previous observation of the only other literature-known Fe(IV)N/Fe(V)N redox pair, namely, [PhB(tBuIm)3FeN]0/+. On the basis of 57Fe Mössbauer, EPR, and UV/vis electronic absorption spectroscopy as well as quantum chemical calculations, we identified the lesser degree of pyramidalization around the iron atom, the Jahn-Teller distortion, and the resulting nature of the SOMO to be the decisive factors at play.
CRIS-Team Scopus Importer:2021-02-05

Synthesis and Reactivity of a Cobalt-Supported Singlet Nitrene - Mao, Weiqing; Zhang, Zihan; Fehn, Dominik; Jannuzzi, Sergio A.V.; Heinemann, Frank Wilhelm; Scheurer, Andreas; van Gastel, Maurice; DeBeer, Serena; Munz, Dominik; Meyer, Karsten (Journal of the American Chemical Society, 2023)
The synthesis, characterization, and reactivity of a series of cobalt terminal imido complexes supported by an N-anchored tripodal tris(carbene) chelate is described, including a Co-supported singlet nitrene. Reaction of the CoI precursor [(TIMMNmes)CoI](PF6) (TIMMNmes = tris-[2-(3-mesityl-imidazolin-2-ylidene)-methyl]amine) with p-methoxyphenyl azide yields a CoIII imide [(TIMMNmes)CoIII(NAnisole)](PF6) (1). Treatment of 1 with 1 equiv of [FeCp2](PF6) at −35 °C affords a formal CoIV imido complex [(TIMMNmes)Co(NAnisole)](PF6)2 (2), which features a bent Co-N(imido)-C(Anisole) linkage. Subsequent one-electron oxidation of 2 with 1 equiv of AgPF6 provides access to the tricationic cobalt imido complex [(TIMMNmes)Co(NAnisole)](PF6)3 (3). All complexes were fully characterized, including single-crystal X-ray diffraction (SC-XRD) analyses, infrared (IR) vibrational, ultraviolet/visible (UV/vis) electronic absorption, multinuclear NMR, X-band electron paramagnetic resonance (EPR), electron nuclear double resonance (ENDOR), and high-energy-resolution fluorescence-detected X-ray absorption spectroscopy (HERFD XAS). Quantum chemical calculations provide additional insight into the electronic structures of all compounds. The dicationic CoIV imido complex 2 exhibits a doublet ground state with considerable imidyl character as a result of covalent Co-NAnisole bonding. At room temperature, 2 readily converts to a CoII amine complex involving intramolecular C-H bond amination. Electronically, tricationic complex 3 can be understood as a singlet nitrene bound to CoIII with significant CoIV imidyl radical character. Verifying the pronounced electrophilicity, nucleophiles such as H2O and tBuNH2 add to 3─analogous to the parent free nitrene─in the para position of the aromatic substituent, thus, clearly corroborating singlet nitrene-type reactivity.
CRIS-Team Scopus Importer:2023-07-21

The synthesis and characterization of an iron(VII) nitrido complex - Keilwerth, Martin; Mao, Weiqing; Malischewski, Moritz; Jannuzzi, Sergio A.V.; Breitwieser, Kevin; Heinemann, Frank Wilhelm; Scheurer, Andreas; DeBeer, Serena; Munz, Dominik; Bill, Eckhard; Meyer, Karsten (Nature Chemistry, 2024)
Complexes of iron in high oxidation states are captivating research subjects due to their pivotal role as active intermediates in numerous catalytic processes. Structural and spectroscopic studies of well-defined model complexes often provide evidence of these intermediates. In addition to the fundamental molecular and electronic structure insights gained by these complexes, their reactivity also affects our understanding of catalytic reaction mechanisms for small molecule and bond-activation chemistry. Here, we report the synthesis, structural and spectroscopic characterization of a stable, octahedral Fe(VI) nitrido complex and an authenticated, unique Fe(VII) species, prepared by one-electron oxidation. The super-oxidized Fe(VII) nitride rearranges to an Fe(V) imide through an intramolecular amination mechanism and ligand exchange, which is characterized spectroscopically and computationally. This enables combined reactivity and stability studies on a single molecular system of a rare high-valent complex redox pair. Quantum chemical calculations complement the spectroscopic parameters and provide evidence for a diamagnetic (S = 0) d 2 Fe(VI) and a genuine S = 1/2, d 1 Fe(VII) configuration of these super-oxidized nitrido complexes. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2024-02-09

Umpolung in a Pair of Cobalt(III) Terminal Imido/Imidyl Complexes - Mao, Weiqing; Fehn, Dominik; Heinemann, Frank Wilhelm; Scheurer, Andreas; Van Gastel, Maurice; Jannuzzi, Sergio A.; Debeer, Serena; Munz, Dominik; Meyer, Karsten (Angewandte Chemie International Edition, 2022)
Reaction of the CoI complex [(TIMMNmes)CoI](PF6) (1) (TIMMNmes=tris-[2-(3-mesityl-imidazolin-2-ylidene)-methyl]amine) with mesityl azide yields the CoIII imide [(TIMMNmes)CoIII(NMes)](PF6) (2). Oxidation of 2 with [FeCp2](PF6) provides access to a rare CoIII imidyl [(TIMMNmes)Co(NMes)](PF6)2 (3). Single-crystal X-ray diffractometry and EPR spectroscopy confirm the molecular structure of 3 and its S= (Formula presented.) ground state. ENDOR, X-ray absorption spectroscopy and computational analyses indicate a ligand-based oxidation; thus, an imidyl-radical electronic structure for 3. Migratory insertion of one ancillary NHC to the imido ligand in 2 gives the CoI N-heterocyclic imine (4) within 12 h. Conversely, it takes merely 0.5 h for 3 to transform to the CoII congener (5). The migratory insertion in 2 occurs via a nucleophilic attack of the imido ligand at the NHC to give 4, whereas in 3, a nucleophilic attack of the NHC at the electrophilic imidyl ligand yields 5. The reactivity shunt upon oxidation of 2 to 3 confirms an umpolung of the imido ligand.
CRIS-Team Scopus Importer:2022-08-12
Keywords: Cobalt; Imidyl Radical; N-Heterocyclic Carbene; Terminal Imido; Umpolung